2018
DOI: 10.1038/s41598-018-24674-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous DNA prime-protein boost immunization with RecA and FliD offers cross-clade protection against leptospiral infection

Abstract: The emergence of >300 serovars of Leptospira confounded the use of generalized bacterin, the whole cell lysate, as vaccines to control leptospirosis. Because of substantial genetic and geographic heterogeneity among circulating serovars, one vaccine strain per serovar cannot be efficacious against all the serovars. We have performed heterologous DNA prime-protein boost vaccination challenge studies in hamsters using in vivo expressed, leptospiral recombinase A (RecA) and flagellar hook associated protein (FliD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Other than Ligs and LipL32, LipL41 has been tested as a vaccine candidate without success ( Ko et al, 2009 ) and LIC20172 and LIC11966 have been identified and tested, respectively, as promising candidates for subunit vaccine ( Lata et al, 2018 ; Oliveira et al, 2018 ). More recently, a DNA vaccine delivering two leptospiral proteins (RecA and FliD) has shown promising results including high survival rates, sterilizing immunity and heterologous protection, although tested only among two different L. interrogans strains ( Raja et al, 2018 ). A major limitation for vaccine development for leptospirosis is the lack of evidence whether immunological correlates from experimental animals are relevant to human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other than Ligs and LipL32, LipL41 has been tested as a vaccine candidate without success ( Ko et al, 2009 ) and LIC20172 and LIC11966 have been identified and tested, respectively, as promising candidates for subunit vaccine ( Lata et al, 2018 ; Oliveira et al, 2018 ). More recently, a DNA vaccine delivering two leptospiral proteins (RecA and FliD) has shown promising results including high survival rates, sterilizing immunity and heterologous protection, although tested only among two different L. interrogans strains ( Raja et al, 2018 ). A major limitation for vaccine development for leptospirosis is the lack of evidence whether immunological correlates from experimental animals are relevant to human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other than Ligs and LipL32, LipL41 has been tested as a vaccine candidate without success 2 and LIC20172 and LIC11966 have been identified and tested, respectively, as promising candidates for subunit vaccine 43,44 . More recently, a DNA vaccine delivering two leptospiral proteins (RecA and FliD) has shown promising results including high survival rates, sterilizing immunity and heterologous protection, although tested only among two different L. interrogans strains 45 . A major limitation for vaccine development for leptospirosis is the lack of evidence whether immunological correlates from experimental animals are relevant to human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several antigens of Leptospira spp. have been evaluated, many of them with potential for vaccine development (Conrad et al, 2017;da Cunha et al, 2019;Ghazali-Bina et al, 2019;Oliveira et al, 2019;Oliveira et al, 2018;Raja et al, 2018) or diagnosis (Alizadeh et al, 2014;Deneke et al, 2014;Nagalingam et al, 2015;Padilha et al, 2019;Shiokawa et al, 2016;Ye et al, 2014). As reported in other spirochetes, the Leptospira spp.…”
Section: Antigens Of Leptospira Spp Used In Diagnosismentioning
confidence: 99%
“…The onset of symptoms typically begins with the appearance of agglutinating antibodies, which increases with disease progression (Lessa-Aquino et al, 2017). This type of response occurs against LPS and several proteins that are constitutively expressed or upregulated during infection (Adler & de la Pena Moctezuma, 2010;Raja et al, 2018). However, IgM isotype antibodies appear approximately four days after symptom onset;…”
Section: Serological and Immunochemical Testsmentioning
confidence: 99%